A New Classification Framework for Urban Geospatial Web Sites - Claude Caron (Unité Mixte de Recherche 8504 Géographie-cités, 2005)
For a few years now, several development projects have been carried out in municipal contexts in order to make spatial information available on the Internet. An overall observation of the existing municipal Web sites obviously shows the great variety of the objectives at stake, and of the technological solutions implemented. Despite the increasing number of researches dealing with the democratization of e-information addressed to citizens and e-governments, it is still difficult to clearly identify the current privileged means of communication between cities and citizens on the basis of cartographic data. This difficulty is related to the absence of formal and effective frameworks to characterize and classify the various ways to diffuse geospatial information on municipal Web sites. On the basis of the above, the present research aims at remedying this ignorance by elaborating a new classification framework to effectively describe GIS-based Web sites in municipal contexts. The adopted strategy consists in analysing the already existing partial approaches of classification, in order to pursue with the development of a more comprehensive pragmatic classification framework. This framework is then the subject of an experimentation consisting of a detailed analysis of the contents and functioning of a hundred existing municipal Web sites in Canada. Finally, this experimentation makes it possible to draw initial conclusions regarding the usability of the new classification mode proposed, as well as to identify some further research pathways.